Effects of salinity and temperature on growth and ultrastructure of Tetraselmis tetrathele (West) Butcher, 1959 - Lai, Dora Jang Ing (2013)
The effects of salinity and temperature on the growth and ultrastructure of Tetraselmis tetrathele were evaluated in this study. Seven salinity levels (0, 10, 20, 30, 40, 50 and 60 ppt) were examined with a 12h:12h lightdark cycle under light intensity of 67.5 ~mol/m2 s. Effects of temperature on the growth and ultrastructure of T. tetrathele was carried out at 25°C and 30°C at the salinity of 30 ppt with other culture conditions similar (12h:12h L:O; 67.5 umol/rn" s) to those used in salinity experiment. After execution of the studies with salinity and temperature, the selected salinity (30 ppt) and temperature, 26±2°C were used to up-scale T. tetrathele using annular photobioreactors with different culture medium (f/2 and Conway medium) in an indoor environment. he specific growth rate of T. tetrathele was lowest (p<0.05) at 0 ppt. However, the growth rates of T. tetrathele did not differ significantly (p>0.05) in 10, 20, 30, 40, 50 and 60 ppt. The study revealed that T. tetrathele thrived best in 40 ppt. Upon exposure for 30 minutes, transmission electron micrographs of T. tetrathele revealed that cells were surrounded with a few layers of thecae and chloroplast of the cells were filled with starch and lipid. After 4 days of cultivation, layers of thecae, amount of lipid and starch decreased in all the treatments. The specific growth rate of T. tetrathele at 30°C (0.24/day) was significantly lower to those grown in 25°C (0.63/day). Numerous starch plates and lipid globules observed in cultures exposed for 30 minutes at 25°C and 30°C. Starch plates and lipid globules were depleted after 4 days of both culture. Electron micrographs of T. tetrathele grown at 30°C revealed that chloroplast structure was loosely stacked in the microalgal cells indicating that cells were unable to withstand high temperatures (30°C). Culture medium did not affect (p>0.05) the growth and biomass production of T. tetrathele grown in indoor photobioreactors. Protein content was affected by growth phases (p<0.05) with a significantly higher percentage (p<0.05) during the exponential phases compared to the stationary phases in both culture medium. Carbohydrate, and lipid contents increased during the stationary phase of both f/2 and Conway enriched cultures. Conway enriched T. tetrathele produced significantly higher (p<0.05) lipid content as compared to f/2 enriched cultures. Polyunsaturated fatty acids (PUFA) were found to be the major proportion in the fatty acid profiles of T. tetrathele. Fatty acids that were found to be major constituents of T. tetrathele were palmitic acid (C16:0), oleic acid (C18:1), linoleic acid (C18:2 n-6) and a-linolenic acid (C18:3 n-3). The results of the present study showed that low salinity (0 ppt) and high temperature (30°C) decreased the growth of T. tetrathele. Both f/2 and Conway medium can be used for the cultivation of T. tetrathele as growth and biomass were comparable in both medium (p>O.OS). Besides that, protein was found to be a major composition (16.00 to 39.00%) in T. tetrathele as compared to carbohydrate (16.00 to 23%), lipid (21.00 to 3S.00%), ash (1S.00 to 23.00%) and moisture (0.10 to 0.30%).